A viscoelastic-viscoplastic model for a thermoplastic and sensitivity of its rheological parameters to the strain-rate (Fracture and Structural Integrity, 2019)
The behavior of thermoplastics depends on several factors, mainly time and temperature. The present work is the subject of an analysis of the dependence of viscoelastic viscoplastic parameters of a model of rheological behavior at the time. The material considered in this study is a polyamide 6. The model of applied behavior is represented by the Kelvin-Voigt viscoelastic mechanism mounted in series with a viscoplastic branch of Bingham. Following a mathematical formulation of the equations governing the model, tensile tests at different strain rates are conducted. The model parameters are then identified by inverse analysis. The technique of genetic algorithms has been favored. A nonlinear dependence of these parameters on the rate of strain has been observed. The dependence function has been established by a nonlinear regression technique. The comparison of the experimental results with those obtained by the model reveals a satisfactory agreement, hence the validation of the approach adopted.
Keywords: Viscoelasticity; Viscoplasticity; Strain-rate; Rheological parameters; Thermoplastic; Genetic algorithms